THE DEVELOPMENT OF EMOTIONAL INTELLIGENCE IN PRESCHOOL-AGED CHILDREN: A PATH TO FUTURE SUCCESS (Conferencea, 2024)
The article explores the significance of emotional intelligence (EI) development in preschool-aged children, emphasizing its role in shaping their social skills, emotional regulation, and cognitive abilities. Strategies for fostering EI through storytelling, games, and teacher-led interventions are discussed, with an emphasis on creating emotionally supportive environments. The findings highlight how EI in early childhood lays the groundwork for academic success and well-being in later life.